Congestion management in restructured power systems - Xiao, Yu (2008)
This thesis aims to study important aspects of the transmission congestions in the restructured environment. The development of congestion mitigation, transmission and congestion pricing and market power assessment are the main contribution of the research. Detailed analysis and studies include an OPF model proposed for congestion mitigation, proportional tree method and its application on transmission usage allocation and congestion cost allocation, and the nodal market power investigation under transmission congestion.